Promoting the energy refurbishment of social housing: the KlimaKit model. (August 2019) - Penna, P; Schweigkofler, A; Brozzi, R; Marcher, C; Matt, D T
Abstract: Despite the well-known need of retrofitting the existing building stock and the availability of a wide range of energy efficient technologies, financial products and public incentives, the private as well as the public sector are struggling to invest in energy efficient solutions for buildings. Designers, companies, financers, and energy suppliers follow their own profit, instead of creating synergies to fulfil what should be the final goal of a retrofitting project: the client's satisfaction. The aim of this paper is to present the methodology developed, within the KlimaKit project [1], to support both the refurbishment process of the buildings belonging to the social housing association of the Autonomous Province of Bolzano and the energy refurbishment market of South Tyrol. The results presented in this paper are part of the ongoing research project "KlimaKit", founded by operational programme European Fund for Regional Development of the Autonomous Province of Bolzano EFRD 2014-2020 – Investments in Growth and Employment.